(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The current paper reports the analysis and design of air quality and human thermal comfort in rooms using impinging jet ventilation system at different occupant distribution. Theoretical and experimental studies at different situations of occupant distribution used the square cross sectional supply air duct with height from the foot level end (0.1h). This work presents a numerical study for predicting the indoor airflow and temperature distribution by adopting impinging jet ventilation system in office room. The emergence of the three zones flow field of an impinging jet is mostly divided into three distinguished zones: impingement zone, wall jet zone and free jet zone which produce excessive kinetic energy at the stagnation zone and distribute approximately in the longitudinal and lateral directions over the floor. Acceptable Air Distribution Performance Index (ADPI), effective temperature and ventilation efficiency were found at situations of occupant distribution (when the occupant located at the center of the room one sitting in front of the other gives optimum human thermal comfort if compared with the other situations of occupant distributions).